Efektivitas Bimbingan Klasikal untuk Meningkatkan Kemampuan Bernalar Kritis Siswa Menggunakan Pendekatan Snowball Throwing - Optimal, Optimal; Ardimen, Ardimen; Irman, Irman; Khairat, Annisaul (FONDATIA, 2023)
The purpose of this study was to find out how effective the classical guidance of the snowball throwing approach was to improve students' reasoning abilities more or less. This type of quantitative research, with an experimental research design. To obtain data from the problems studied, the data collection technique that the authors use is through distributing questionnaires. Data processing was carried out in a quantitative descriptive manner, then described and classified aspects of certain problems and explained through effective sentences according to the concept of guidance and counseling. The results showed that the implementation of the classical snowball throw approach in improving students' critical reasoning abilities after carrying out the N-gain Asymp test. Sig. (2-tailed) for the two-tailed test the significance value of 0.510 is greater than the significance value of 0.169 (0.169 > 0.05). Then H0 is accepted and H1 is rejected, meaning that there is no significant difference in the ability to reason between students in the experimental group who are given classical guidance services using the snowball throwing approach and group students who are given classical guidance services without the snowball throwing approach.